Hitler [videorecording] - Lagone, Patrick; Martin, Kingsley ([S.l.] Granada Production, 1990)
Presents the fury of Adolf Hitler who ruthlessly dominated Europe for over four years inflecting misery and destruction. Included is footage of Hitler's brown-shirted storm troopers and his meetings with Chamberlain, Mussolini and Stalin, as well as his massacre of the Russian people.
VHS.
Credits : Spoken by Brian Cobby.
Keywords: Hitler, Adolf, 1889-1945.; Heads of State -- Germany -- Biography; Germany -- History -- 20th century